The Ripple Effects of Community Science: Experiences of Texas Stream Team Water Quality Monitors - Christina Wright Lopez; Aspen Navarro; Madison Mitchell; Claudia D. Campos; Laura M. Parchman; Jenna J. Walker; Tyler Hartwick; Kaylee Ann Boggan (Citizen Science: Theory and Practice)
Motivations for participation in community science programs are relatively well understood. However, the outcomes of participating in these programs are unclear. As community science is a global phenomenon, scholars and practitioners alike should strive to determine what, if any, long-term effects these programs provide to the individual, society, and the environment. In this qualitative study, we explore the experiences of community scientists involved in the Texas Stream Team program, a long-running community science program focused on surface water quality monitoring in Texas, USA. Using a survey instrument and semi-structured interviews, we asked how individuals became involved, their experiences in discovering pollution events and advocating with data, as well as the impact of program participation on their careers and personal lives. Survey findings (n = 327) reveal reasons for involvement, experiences related to pollution event identification, data utilization, career impacts, and emotional responses. Through interview narratives (n = 21), themes of working through vulnerability, forming place identity, and fostering agency and social capital emerged among community scientists. These narratives revealed personal challenges, budding place attachments, and connection sustained and expanded through ongoing participation. The study emphasizes the multifaceted experiences of community scientists, including outcomes for individual growth, implications for environmental stewardship through transformational learning, and considerations for program infrastructure. It contributes to the literature on community science, volunteer water quality monitoring, and environmental stewardship.